MENUMBUHKAN HARMONI DI SEKOLAH : DINAMIKA PERAN GURU PAI DALAM MENANAMKAN TOLERANSI BERAGAMA DI SMAN 01 LIWA - Arafi, Ahmad Delvin; Jamaluddin, Wan; Hasanah, Uswatun (Reflektika, 2025)
This study aims to examine in depth the dynamics of the role of Islamic Religious Education (PAI) teachers in instilling religious tolerance in students at SMAN 01 Liwa. Using a descriptive qualitative approach, this study explores learning strategies, forms of interfaith collaboration, and the challenges teachers face in practice. The research findings reveal that PAI teachers play a central role as educators, mentors, and facilitators of interfaith dialogue. Key strategies used include integrating tolerance values into course materials, collaborating with teachers of other religions, and organizing interfaith community service activities involving all students. Challenges include the influence of social media, students' low understanding of tolerance, and differences in family education patterns. Overall, the instillation of tolerance at SMAN 01 Liwa is effective through a collaborative approach and direct social experience.